2021
DOI: 10.3390/ph14111132
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone Potentiates the Effect of Phenytoin against Electroshock-Induced Convulsions in Rats by Reducing the Hyperactivation of m-TOR Pathway and Neuroinflammation: Evidence from In Vivo, In Vitro and Computational Studies

Abstract: Epilepsy is a chronic neurodegenerative disease characterized by multiple seizures, hereto 35% of patients remain poor responders. Phenytoin (PHT; 20 and 40 mg/kg) and thymoquinone (THQ; 40 and 80 mg/kg) were given alone and as a low dose combination for 14 days (p.o), prior to challenge with maximal electroshock (MES; 180 mA, 220 V, 0.2 s). Apart from observing convulsions, hippocampal mTOR, IL-1β, IL-6 and TNF-α levels were measured. Hippocampal histomorphological analysis was also conducted. In vitro cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Phenytoin (PHT), also known as 5,5-diphenylhydantoin, was first synthesized as a barbiturate derivative in 1908 by German chemist Heinrich Biltz. Two decades later, animal model studies showed that PHT had the property of electroshock convulsion suppression[ 1 ]. In 1938, Tracy Putnam and H. Houston Merritt found out that PHT was useful as an antiepileptic.…”
Section: Introductionmentioning
confidence: 99%
“…Phenytoin (PHT), also known as 5,5-diphenylhydantoin, was first synthesized as a barbiturate derivative in 1908 by German chemist Heinrich Biltz. Two decades later, animal model studies showed that PHT had the property of electroshock convulsion suppression[ 1 ]. In 1938, Tracy Putnam and H. Houston Merritt found out that PHT was useful as an antiepileptic.…”
Section: Introductionmentioning
confidence: 99%
“…The animal studies as well have confirmed the anti-ictal effect of THQ. Beyazcicek et al, 2016 reported that THQ reduces the incidence of spike waves and epileptic activity and frequency in penicillin-induced seizures [ 29 ], Hosseinzadeh et al, 2005 reported reduction in time to onset of seizures and seizure duration in the PTZ model [ 56 ] and Pottoo et al, 2021 reported reduction in THLE following MES induced seizures in THQ treated rats [ 57 ]. The duo-drug combinatorial therapy of SVP (150 mg/kg) with BFN (5 mg/kg) exhibited anticonvulsant effect, but the efficacy was no better than monotherapy with individual drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy is one of the most heterogeneous neurological disorders, which is characterized by persistent neural activity and recurrent spontaneous seizures. This neurological disorder can occur for a number of reasons, including as a result of traumatic brain injury and genetic factors [70,71]. Violation of the inhibitory-excitatory balance in the brain is considered as an important mechanism of the pathogenesis of epilepsy.…”
Section: Neuroprotective Properties Of Thymoquinone In Modeling Epilepsymentioning
confidence: 99%